Role of Milk Intake in Modulating Serum Lipid Profiles and Gut Metabolites - Xu, Ting; Zhang, Chang; Yang, Yufeng; Huang, Liang; Liu, Qingyou; Li, Ling; Zeng, Qingkun; Li, Zhipeng (Metabolites, 2024)
Background/Objectives: Milk is one of the main sources of nutrition in people’s daily diet, but the fat in milk raises health concerns in consumers. Here, we aimed to elucidate the impact of Buffalo milk and Holstein cow milk consumption on blood lipid health through metabolomics analysis. Methods: Golden hamsters were administered Murrah Buffalo milk (BM) or Holstein cow milk (HM), and the body weight and serum lipid indicators were tested and recorded. The hamsters receiving equal amounts of physiological saline were used as the negative control (NC). Serum and fecal samples were collected, and LC-MS was used to identify the metabolites in the samples. Results: The results showed that both the BM and HM groups exhibited a significant reduction in body weight compared to that of the NC group from day 9, and the serum TG, TC, and LDL-C levels were significantly lower than those of the NC group. Further analysis identified 564 and 567 metabolites in the serum and fecal samples shared in the BM and HM groups and significantly different from those in the NC group, which were mainly enriched in the pathways related to lipid metabolism, such as fatty acid biosynthesis, arachidonic acid metabolism, and primary bile acid biosynthesis. Correlation analysis further suggested that milk intake can increase the levels of Muramic Acid, Oleoyl Ethanolamide, Seratrodast, Chenodeoxycholic Acid, Docosahexaenoic Acid Ethyl Ester, and Deoxycholic Acid in the serum and gut microbiota, which may affect TG, TC, HDL-C, and LDL-C in the serum, and thereby benefit the body’s lipid health. Conclusions: The results further confirmed that milk intake has a beneficial effect on blood lipid health by altering multiple metabolites in the serum and the gut. This study provides novel evidence that milk consumption is beneficial to health and is a reference for guiding people to a healthy diet.